Perlindungan Hukum Korban Tindak Pidana Tabrak Lari di Serang Kota - Anindya Sekar Kirana; Fuqoha Fuqoha; Fitria Agustin (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
A traffic accident in which the perpetrator is not responsible, leaving the victim alone without stopping the vehicle, and not providing assistance is called a hit-and-run. The crime of hit and run is a problem that needs to be addressed because it is an immoral act and harms others. This thesis will be discussed Police Efforts in protecting hit-and-run victims in the Serang City Region and the Police's efforts to deal with obstacles in protecting hit-and-run victims in the Serang City Region. The research method used is empirical juridical, namely examining applicable legal provisions with data obtained in the field, namely the Serang City Police Resort, in the form of processing data on hit-and-run cases by the police and interviews to obtain information about the factors causing the hit-and-run crime, as well as the handling process. by the police in this case. The handling of the hit-and-run by the police is after receiving a report of a traffic accident, going directly to the crime scene (TKP), collecting evidence, and making an official report at the crime scene. After finding the culprit, an investigation is carried out, if an investigation into the hit-and-run case has been carried out and not found sufficient evidence, then the investigation is terminated (SP3). However, if the perpetrator has not been found, the investigation will continue until the perpetrator is found. In handling hit-and-run criminal cases, the police often experience obstacles, including the lack of evidence and witness statements, and the lack of infrastructure and human resources in the traffic unit which results in delays in handling hit-and-run accidents in the Serang City Police District.